2017
DOI: 10.1039/c6ob02369j
|View full text |Cite
|
Sign up to set email alerts
|

Formal nucleophilic borylation and borylative cyclization of organic halides

Abstract: This review describes recent advances in direct borylation reactions of organic halides, including both transition-metal-catalyzed and metal-free methods. Since the pioneering work on palladium-catalyzed boryl substitution of aryl halides with a diboron compound reported by Miyaura and co-workers in 1995, various catalytic systems for the borylation of aryl, alkneyl, and alkyl halides have been developed to give a wide range of organoboronate esters that cannot be synthesized using conventional methods. Boryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(44 citation statements)
references
References 96 publications
0
44
0
Order By: Relevance
“…Higher yields have traditionally been associated with three structural features: a more stable organocopper intermediate, more reactive methyl, allylic and benzylic electrophiles, [72][73][74] and an intramolecular 'alkylation' step. [75][76][77] For example, allene-derived boracuprates can be coupled with allylic phosphates in an S N 2 0 process (Scheme 16i), and a range of cycloalkyl boronate esters (Scheme 16ii-iv) have been synthesised by the intramolecular bora-alkylation of vinylsilanes and styrenes, in which the anion stabilising group facilitates and directs the boracupration step. [77][78][79] A larger range of primary alkyl halides can be used in intermolecular alkylation of butenyl ethers wherein the heteroatom can coordinate and stabilise the organocopper intermediate (Scheme 16v).…”
Section: Reactions Of Copper-boryl Species With C-c Multiple Bondsmentioning
confidence: 99%
“…Higher yields have traditionally been associated with three structural features: a more stable organocopper intermediate, more reactive methyl, allylic and benzylic electrophiles, [72][73][74] and an intramolecular 'alkylation' step. [75][76][77] For example, allene-derived boracuprates can be coupled with allylic phosphates in an S N 2 0 process (Scheme 16i), and a range of cycloalkyl boronate esters (Scheme 16ii-iv) have been synthesised by the intramolecular bora-alkylation of vinylsilanes and styrenes, in which the anion stabilising group facilitates and directs the boracupration step. [77][78][79] A larger range of primary alkyl halides can be used in intermolecular alkylation of butenyl ethers wherein the heteroatom can coordinate and stabilise the organocopper intermediate (Scheme 16v).…”
Section: Reactions Of Copper-boryl Species With C-c Multiple Bondsmentioning
confidence: 99%
“…Indeed, we envisioned that we could further elaborate these substructures by executing C sp 2 –C sp 3 photoredox cross-coupling, 10 Suzuki cross-coupling, 11 Buchwald–Hartwig amination, 12 and palladium-mediated borylation. 13 After functionalization, the relatively mild nature of dehydrative elimination would furnish structurally complex Îą-trifluoromethyl alkenes. The amenability of Îą-trifluoromethyl-β-silyl alcohols toward Suzuki–Miyaura coupling was first investigated.…”
Section: Resultsmentioning
confidence: 99%
“…However, we envisioned the chlorine group being readily installed via the pinacol boronic ester ultimately to afford malbrancheamide B ( 17 ). Although various methods for the conversion of aryl iodides and bromides into the corresponding pinacol boronic esters are known 37 , we found that the photoirradiation methods of Larionov and co-workers 38 and of Li and co-workers 39 were the most effective for our purpose. The boronic ester was carried on to 17 , as illustrated in Fig.…”
mentioning
confidence: 78%